Employees Work Behavior at Lis Cosmetic Shop - Sulastri, Leonard Adrie Manafe (LPPPIPublishing, 2022)
This study aims to analyze the work behavior of employees at the Lis Cosmetic Store (LCS). The unit of analysis that will be observed is the work behavior of employees at the LCS using a qualitative approach and implementing a case study method. The research includes indicators of work behavior, namely work quality, expertise, social relations, self-confidence, self-control, and work habits. Data collection was done by using interviews and observation. From the research that has been done, it is known that there are differences in work behavior among employees with the emergence of performance in employees which is influenced by several factors, differences in basic skills, and personality of each employee. The work environment and targets also have a very positive effect on employee work behavior and it is known that the trigger for the emergence of attitudes in employee work behavior is influenced by the desire, and it is related to wages, bonuses, and compensation provided by the company. Other triggers relate to promotions, promotions, and recognition of employee performance contributions in the form of praise for achievements that have been achieved.